(untitled) (Colloquia Comparativa Litterarum, 2025)
In his article "Major Histories, Minor Literatures, and World Authors" Theo D’haen discusses how the idea of world literature has made a remarkable comeback in literary studies. A major feature of this revival has been increased attention from a "world perspective" to literatures until recently little studied beyond disciplinary boundaries, particularly so some "major" literatures such as Chinese, Japanese, Arabic, and various Indian-language literatures. As such, these literatures have come to join what has usually been thought of as "European" world literature. What this move, however to be welcomed in itself, obscures is the even further peripheralization of a number of "smaller" literatures, amongst them many European ones. Thus world literature in its newly emerging guise is merely upping the ante for such minor literatures, or, alternatively, reshaping such literatures in the image and interest of the few "major" literatures which are deemed worthy of inclusion in the "new" world literature.